Distinguishing emptiness from nothingness - Rošker, Jana S. (Asian studies, 2025)
The philosophical definition of the relationship between nothingness and emptiness continues to spark academic debates and controversies. In this article, we aim to clarify this relationship by examining some Chinese discourses relevant to the topic. The concept of absolute nothingness, as it was established in the Neo-Daoist philosophy of the Wei-Jin period in China—and reaching perhaps its most sophisticated form in the philosophy of Nishida Kitaro within the Kyoto School—must be distinguished from emptiness in the sense of the absence of substance, which forms the basis of various philosophical discussions in Sinicized Buddhism and continues to resonate in certain epistemological theories of contemporary Chinese scholars. In this paper, I will first provide a brief introduction to these theories of knowledge, with a particular focus on the contributions of the modern Chinese philosopher Zhang Dongsun, whose work was shaped by the classical Chinese paradigm of structural interrelations on the one hand, and the principles of Sinicized Buddhism on the other. In conclusion, I will juxtapose the theoretical foundations of these epistemologies with the aforementioned conceptualizations of nothingness, thereby attempting to elucidate the relationship between these two seemingly related concepts.
Keywords: coherence; emptiness; koherenca; nič; nothingness; praznina; relacijska struktura; relational structure; Zhang Dongsun